Effect of Psidium cattleianum leaf extract on Streptococcus mutans viability, protein expression and acid production - Brighenti, Fernanda Lourenção [UNESP]; Luppens, S. B. I.; Delbem, Alberto Carlos Botazzo [UNESP]; Deng, D. M.; Hoogenkamp, M. A.; Gaetti-Jardim, E. [UNESP]; Dekker, H. L.; Crielaard, W.; ten Cate, J. M. (Karger, 2008)
Plants naturally produce secondary metabolites that can be used as antimicrobials. The aim of this study was to assess the effects of Psidium cattleianum leaf extract on Streptococcus mutans. The extract (100%) was obtained by decoction of 100 g of leaves in 600 ml of deionized water. To assess killing, S. mutans biofilms were treated with water (negative control) or various extract dilutions [ 100, 50, 25% (v/v) in water] for 5 or 60 min. To evaluate the effect on protein expression, biofilms were exposed to water or 1.6% (v/v) extract for 120 min, proteins were extracted and submitted to 2-dimensional difference gel electrophoresis. Differentially expressed proteins were identified by mass spectrometry. The effect of 1.6% (v/v) extract on acid production was determined by pH measurements and compared to a water control. Viability was similar after 5 min of treatment with the 100% extract or 60 min with the 50% extract (about 0.03% survival). There were no differences in viability between the biofilms exposed to the 25 or 50% extract after 60 min of treatment (about 0.02% survival). Treatment with the 1.6% extract significantly changed protein expression. The abundance of 24 spots was decreased compared to water (p < 0.05). The extract significantly inhibited acid production (p < 0.05). It is concluded that P. cattleianum leaf extract kills S. mutans grown in biofilms when applied at high concentrations. At low concentrations it inhibits S. mutans acid production and reduces the expression of proteins involved in general metabolism, glycolysis and lactic acid production. Copyright (C) 2008 S. Karger AG, Basel.
Keywords: antibacterial agents; plant extract; proteome; Streptococcus mutans